Longitudinal assessment of gender differences in the development of PTSD among US military personnel deployed in support of the operations in Iraq and Afghanistan. (September 2015) - Jacobson, Isabel G.; Donoho, Carrie J.; Crum-Cianflone, Nancy F.; Maguen, Shira
Abstract: Divergent findings from previous research examining gender differences in the development of posttraumatic stress disorder (PTSD) among US military members deployed to the operations in Iraq or Afghanistan (recent operations) prompted this study utilizing a matching approach to examine whether risk for new-onset PTSD and PTSD severity scores differed by gender. US military members from the Millennium Cohort Study deployed in support of the recent operations were followed for approximately 7 years from baseline through 2 follow-up periods between 2001 and 2008. Propensity score matching was used to match 1 male to each female using demographic, military, and behavioral factors including baseline sexual assault. Analyses were stratified by combat experience defined as reporting at least one of five exposures during follow-up. Outcome measures included a positive screen for PTSD and severity scores measured by the PTSD Patient Checklist–Civilian Version. Discrete-time survival analysis quantified the association between gender and incident PTSD. Among 4684 matched subjects (2342 women and men), 6.7% of women and 6.1% of men developed PTSD during follow-up. Results showed no significant gender differences for the likelihood of developing PTSD or for PTSD severity scores among women and men who reported combat experience and among those who did not. This study is the first of its kind to match a large population of male and female service members on important baseline characteristics including sexual assault. Findings suggest that while combat deployed personnel develop PTSD, women do not have a significantly different risk for developing PTSD than men after experiencing combat. Highlights: Male and female military personnel were matched on baseline characteristics. Lifetime history of sexual assault was included in the matching criteria. Statistical adjustment for sexual assault during follow-up was included in models. Combat experience was controlled for by stratification. Likelihood for incident PTSD and PTSD severity scores were similar by gender.